Prevalence of Pollen Allergen Sensitization Among Atopic Filipino Patients seen in Specialty Clinics in Three Areas of Luzon from 2021 to 2023 - Gonzales-Montalbo, Michaela Ann; Kwong-Buizon, Shirley (Philippine Journal of Allergy, Asthma and Immunology, 2025)
Objectives: This study aims to determine the prevalence of pollen sensitization, as assessed by skin prick testing, among patients with allergic rhinitis, bronchial asthma, and atopic dermatitis in three areas of Luzon: the National Capital Region (NCR), North Luzon, and South Luzon. Methodology: This was a cross-sectional chart review of skin prick test results conducted in NCR, North Luzon, and South Luzon from 2021 to 2023. Demographic and clinical data were collected and analyzed. Descriptive statistics were used to summarize demographic and clinical characteristics. Associations with pollen sensitization were analyzed using Fisher’s exact test, with the level of significance set at 5%. Results and Conclusion: A total of 355 patients were included (97 from NCR, 102 from North Luzon, and 156 from South Luzon), of whom 63.1% demonstrated pollen sensitization. Grass pollens were the most prevalent allergens, particularly carabao grass, Bermuda grass, and pigweed. A significant association was observed between pollen sensitization and both age and season. Climatological changes, urbanization, and differences in vegetative growth may have influenced the pollen sensitization profiles across the three areas.